(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Analysis of mythical-historical legends about the origin of the Lordship of Biscay, based on comparative literature and mythology. Pro- tagonists and themes of these narrations are characteristic of Celtic literature and reveal an underlying Celtic mythological background, previously ignored, in the popular imaginary of Basque people. This analysis of Celtic-Basque literature offers logical difficulties dues to the contaminations sustained over time, but the differentiation of this Celtic-Basque literature from the Euskaldun one represents a clear progress, be- cause until now both were confused. This important Celtic-Basque literary tradition has its roots in the Celtic peoples of Basque Country in Antiquity. It allows a better understanding of the origins of the Basque literature, and con- firms the linguistics, archaeological and DNA data on the ethnogenesis of the Basque Country, which offers very deep Celtic roots.